[RETRACTED] HUBUNGAN ANTARA PERCEIVED SOCIAL SUPPORT DENGAN SUBJECTIVE WELL-BEINGPADA PURNAWIRAWAN TNI - I Gusti Ayu Putu M.J.; Setiasih Setiasih (CALYPTRA, 2019)
[THIS ARTICLE HAS BEEN RETRACTED] Following a rigorous, carefully concerns and considered review of the article published in CALYPTRA to article entitled "HUBUNGAN ANTARA PERCEIVED SOCIAL SUPPORT DENGAN SUBJECTIVE WELL-BEINGPADA PURNAWIRAWAN TNI" Vol.7 No 2, pp.3691-3709, March 2019 The document and its content has been removed from CALYPTRA, and reasonable effort should be made to remove all references to this article.